Coupling of alternative splicing and alternative polyadenylation - Zhang Xueying; Liu Feiyan; Zhou Yu (Acta Biochimica et Biophysica Sinica)
RNA splicing and 3′-cleavage and polyadenylation (CPA) are essential processes for the maturation of RNA. There have been extensive independent studies of these regulated processing events, including alternative splicing (AS) and alternative polyadenylation (APA). However, growing evidence suggests potential crosstalk between splicing and 3′-end processing in regulating AS or APA. Here, we first provide a brief overview of the molecular machines involved in splicing and 3′-end processing events, and then review recent studies on the functions and mechanisms of the crosstalk between the two processes. On the one hand, 3′-end processing can affect splicing, as 3′-end processing factors and CPA-generated polyA tail promote the splicing of the last intron. Beyond that, 3′-end processing factors can also influence the splicing of internal and terminal exons. Those 3′-end processing factors can also interact with different RNA-binding proteins (RBPs) to exert their effects on AS. The length of 3′ untranslated region (3′ UTR) can affect the splicing of upstream exons. On the other hand, splicing and CPA may compete within introns in generating different products. Furthermore, splicing within the 3′ UTR is a significant factor contributing to 3′ UTR diversity. Splicing also influences 3′-end processing through the actions of certain splicing factors. Interestingly, some classical RBPs play dual roles in both splicing and 3′-end processing. Finally, we discuss how long-read sequencing technologies aid in understanding the coordination of AS-APA events and envision that these findings may potentially promote the development of new strategies for disease diagnosis and treatment.